Senegalese immigration in Argentina during the last two decades. An analysis of legal status and the situation regarding the economic, social and cultural rights (2019)
Considering the Saharan population growth in Argentina, this article investigates, in existing studies and documents, the causes and characteristics of migration. From this review the author aims to know the conditions of the Senegalese population with respect to the protection of fundamental rights. In this sense it refers to International Law through the International Covenant on Economic Social and Cultural Rights, and its correspondence with the Argentinian legislation, based on the law 25,871, in order to verify its fulfi llment within this group of immigrants. The sources correspond to the current legislation, studies carried out, and a complaint of Senegalese migrants, speeches, articles and publications of the organizations involved in the migration area.